Investigating the Contact Responses of the Roller Cavity Surfaces in the Compressor Blade Rolling Process. (30th June 2020) - Jin, Qichao; Wang, Wenhu; Jiang, Ruisong
Abstract : The investigation of the contact responses is the key for evaluating the local wear of dies in the plastic forming process. This paper investigated the contact load distributions and evolutions of the roller cavities in the compressor blade rolling process by the FEM. It was the first study to quantify the distributions and evolutions of the contact responses for rolling irregular components. The results indicated that the maximum contact pressure is generally present at the center of the contact interfaces, and the magnitudes of contact pressure decreased with evolution of the blade rolling process. The rolling contact interfaces can be divided into the backward slip zone, the stick zone, and the forward slip zone based on the shear stress distributions. The stick zone was a narrow belt which separated the forward and the backward slip zone, and the shear stress in the stick zone was nearly zero. The shear stress magnitudes in the forward slip zone were smaller than those in the backward slip zone, and the directions of shear stress in forward and backward slip zones were adverse. The magnitudes of shear stress over the forward and backward slip zones decreased with evolution of the blade rolling process. The distributions of local sliding were in a V-shape, the local sliding in the stick zone was nearly zero, and the bigger sliding in backward and forward slip zones was present at the boundaries of rolling entrance and exit sections. The local sliding velocity magnitudes in the backward slip zones were always bigger than those in the forward slip zones, and the magnitudes of local sliding at the rolling entrance sections were bigger than those at the rolling exit sections. In general, the local sliding velocity magnitudes increased firstly and decreased sharply at 2 T /3. The current paper develops the distributions and evolutions of contact responses in the blade rolling process. The contact responses can be used for studying the wear of roller cavities to avoid the accuracy inconsistency of the shaped blade.